Human-Centered Technology for a Better Tomorrow Proceedings of HUMENS 2021 - Hassan, Mohd Hasnun Arif.; Ahmad (a) Manap, Zulkifli; Baharom, Mohamad Zairi; Johari, Nasrul Hadi.; Jamaludin, Ummu Kulthum; Jalil, Muhammad Hilmi; Mat Sahat, Idris; Omar, Mohd Nadzeri; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book acts as a compilation of papers presented in the Human Engineering Symposium (HUMENS 2021). The symposium theme, (3z(BHuman-centered Technology for A Better Tomorrow,(3y (Bcovers the following research topics: ergonomics, biomechanics, sports technology, medical device and instrumentation, artificial intelligence / machine learning, industrial design, rehabilitation, additive manufacturing, modelling and bio-simulation, and signal processing. Fifty-nine articles published in this book are divided into four parts, namely Part 1$1 (BArtificial Intelligence and Biosimulation, Part 2$1 (BBiomechanics, Safety and Sports, Part 3$1 (BDesign and Instrumentation, and Part 4$1 (BErgonomics.s
Heart Rate Variability (HRV) as a Physiological marker of Stress among Electronics Assembly Line Workers -- Dynamic Propagation Area to Simulate Soft Tissue De- formations using Mass Spring Method -- MG Signal Segmentation to Predict Driver's Vigilance State -- Prediction of Blood Glucose Level based on Lipid Profile and Blood Pressure using Multiple Linear Regression Model -- Study on the Enhancement of Malaysian ICU Centre and Introduction of STAR Performance -- Modeling of Soft Tissue Deformation using Mass Spring Method with Nonlinear Volume Force -- Chaotic Map Initializations with Tiki-Taka Algorithm for Software Remodularization Problem -- Development of Real-time Emotion Recognition System Based on Machine Learning Algorithm -- Development of Sign Language Translator for Speech Impairment Person -- Comparative Study of Five Metaheuristic Algorithms for Team Formation Problem -- Automatic Identification of Plastic Waste By HSV Colour -- Validation of compressive test of biodegradable lumbar interbody spinal cage with different porous structure using computed tomography-based finite element analysis -- Node-Based Soft Object Deformation using Stress Estimation Method -- Effect of Airway Stent on Stenosed Trachea.
Keywords: Biomedical engineering; Biomechanics; Sports sciences; Recreation -- Equipment and supplies; Biomechanical Analysis and Modeling; Biomechanics; Sport Technology; Human engineering -- Congresses